Voting Behavior of Voters in Banica, Roxas City - Gigawin, Randy R. (JPAIR Multidisciplinary Research, 2009)
This descriptive-correlational study determined the voting behavior of voters in Banica, Roxas City. The respondents were 246 randomly selected registered voters taken from 18 polling precincts using the stratified proportional sampling. The data needed were gathered using the researcher-made Social Group Context Voting Behavior Questionnaire and Attitudinal Context Voting Behavior Questionnaire that underwent content and construct validation and reliability analysis. The statistical tools used were mean, standard deviation, t-test for independent samples, One-way ANOVA, and Multiple Regression (Enter Method). Under the social group context, voters were generally regionalist except those who have not availed formal schooling and have reached masters' level and above that were found to be popularity oriented and those who were earning P 10,001 to P 20,000 and Non-Roman Catholic that were found to be particularistic. For their voting behavior under the attitudinal context, voters were typically idealistic except those who have reached elementary level that were found to be pragmatic and voters who were earning P 20,001 and above that were issue-oriented. In addition, their voting behavior under the social group context did not significantly differ when classified according to their age, sex, educational attainment, monthly income level, and religion.
Keywords: Voting behavior; voters; Banica; Roxas City